Musical Expectancy. Bridging Music Theory, Cognitive and Computational Approaches - Martin Rohrmeier (Zeitschrift der Gesellschaft für Musiktheorie)
This article contributes to an interdisciplinary discussion of ways in which music-theoretical, cognitive, and computational accounts of musical expectancy may be bridged. It introduces some fundamental concepts concerning modeling, computation, representation, and some of their implications for theory building. Taking Markov models as a case in point, this paper illustrates in detail core notions of representation, model structure, parameter estimation, context-dependency, sparsity and overfitting, as well as the distinction between different levels of expectancy (short-term vs. long-term and knowledge-driven vs. data-driven vs. veridical) that interact in the context of musical listening. The final part compares local and hierarchical accounts of music and analyzes phenomena of nested implication-realization patterns, revision, and garden-path effects.